LEARNING MATERIALS: THE “NUCLEUS” OF LANGUAGE TEACHING - Desy Damayanti; Adin Fauzi; Azizatul Mahfida Inayati (Universitas Sembilanbelas November Kolaka, 2018)
Among some components of effective language classroom, learning materials indisputably play a focal role. They improve the quality of language teaching; facilitate teachers in doing their duties, and lead students to a higher level of understanding in learning. This research aims to discuss the notion of materials in language teaching. It made use of works of literature to outline the importance of materials in language teaching, and to analyze kinds of materials, which are relevant to language teaching. The analysis resulted in the classification of materials into two broad categories namely (1) created materials, which include course book, audio materials, and video materials; and (2) authentic materials, which cover authentic texts, movie/film, radio broadcasting, television program, graphs, maps, tables, and charts. This paper serves as an invaluable resource to facilitate language teachers in selecting appropriate materials for effective language teaching.